Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858437
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Debt in Student Life

Abstract: The amount of sleep college students receive has become a pressing societal concern. While studies show that information technology (IT) use affects sleep, here we examine the converse: how sleep duration might affect IT use. We conducted an in situ study, and logged computer and phone use and collected sleep diaries and daily surveys of 76 college students for seven days, all waking hours. We examined effects of sleep duration and sleep debt. Our results show that with less sleep, people report higher perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Consistent with previous cross-sectional studies that demonstrated that media multitasking was associated with sleep problems (e.g., Calamaro et al, 2009;Mark et al, 2016), our findings showed a near to medium positive relationship between media multitasking and sleep problems in each of the three waves. Adolescents who engaged in higher levels of media multitasking reported more sleep problems.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous cross-sectional studies that demonstrated that media multitasking was associated with sleep problems (e.g., Calamaro et al, 2009;Mark et al, 2016), our findings showed a near to medium positive relationship between media multitasking and sleep problems in each of the three waves. Adolescents who engaged in higher levels of media multitasking reported more sleep problems.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, these deficits in executive functions may lead to an increase in media multitasking (e.g., Baumgartner et al, 2014;Yang & Zhu, 2015). In line with this, Mark et al (2016) found that adolescents who experienced more sleep problems reported more media multitasking the next day. These findings suggest that sleep problems have a proximal effect on media multitasking, but that this effect may not be visible anymore three-to-four months later.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations